Ophthalmic Zoster Infection Presenting with Internal Carotid Artery Vasculitis - ERTAN, Sibel; BENBİR, Gülçin and ÖZEKMEKCİ, Sibel and Albayram, Sait (Cerrahpaşa Medical Journal, 2014)
Cerebral vasculitis is a rare complication of herpes zoster virus infection. In the presented case, 51 year-old man has admitted with left-sided headache, left periorbital edema, ptosis and chemosis, and he was diagnosed as thrombotic vasculitis of internal carotid artery by cranial magnetic resonance and angiographic imagings. After the initiation of methylprednisolone therapy, typical maculopapular herpetic rash over the ophthalmic branch of trigeminal nerve appeared, the diagnosis of herpetic vasculitis and conjuctivitis was made. In this case, it is emphasized that postherpetic cerebral vasculitis can be observed at asymptomatic phase, and, as its complications could be prevented, early diagnosis and treatment of herpes zoster virus infection is important.